An efficient PeT based fluorescent probe for mapping mitochondrial oxidative stress produced via the Nox2 pathway. Issue 13 (15th March 2022) - Baruah, Mousumi; Jana, Anal; Ali, Mudassar; Mapa, Koyeli; Samanta, Animesh
Abstract : A new pentacyclic pyridinium-based mitochondria-specific fluorescent probe, PM-S, exhibited a specific turn-on fluorescence response towards hypochlorous acid and enabled imaging of oxidative stress in mitochondria through Nox2 activation. Abstract : The human innate immune system eliminates invading pathogens through phagocytosis. The first step of this process is activating the nicotinamide adenine dinucleotide phosphate oxidase (Nox2) that utilizes NADPH to produce superoxide anion radicals and other reactive oxygen species (ROS). These ROS then alter the mitochondrial membrane potential and increase peroxide in the mitochondria. The peroxide reacts with myeloperoxidase (MPO) and chloride ions to produce pro-inflammatory oxidant hypochlorous acid (HOCl), which causes oxidative stress leading to cell death. The adverse effects of HOCl are highly associated with cardiovascular disease, neurodegenerative disorders, acute lung injuries, inflammatory diseases, and cancer. Therefore, mapping HOCl in the Nox2 pathway is crucial for an in-depth understanding of the innate immune system. Herein, we developed a unique pentacyclic pyridinium probe, PM-S, that exhibited efficient photoinduced electron transfer (PeT) with HOCl triggered methyl(phenyl)sulfane. PM-S showed several advantages, including better chemical stability, large Stokes shifts (>6258 cm −1 ), high sensitivity (∼50 nM) and specificity to mitochondria, compared to its parent pyrylium PY-S derivative. This probe is also efficient in studying the HOCl produced via the Nox2 pathway in HepG2 and HeLa cells. Analysis using a simple microplate reader and FACS analysis with various inhibitors and inducers supported the mechanistic understanding of Nox2, which can offer an advanced platform for monitoring the inflammatory process more efficiently.